The role of self-regulatory efficacy, moral disengagement and guilt on doping likelihood: A social cognitive theory perspective - Ring, C.; Kavussanu, M. (Journal of Sports Sciences, 2018)
Given the concern over doping in sport, researchers have begun to explore the role played by self-regulatory processes in the decision whether to use banned performance-enhancing substances. Grounded on Bandura`s (1991) theory of moral thought and action, this study examined the role of self-regulatory efficacy, moral disengagement and anticipated guilt on the likelihood to use a banned substance among college athletes. Doping self-regulatory efficacy was associated with doping likelihood both directly (b = -.16, P < .001) and indirectly (b = -.29, P < .001) through doping moral disengagement. Moral disengagement also contributed directly to higher doping likelihood and lower anticipated guilt about doping, which was associated with higher doping likelihood. Overall, the present findings provide evidence to support a model of doping based on Bandura`s social cognitive theory of moral thought and action, in which self-regulatory efficacy influences the likelihood to use banned performance-enhancing substances both directly and indirectly via moral disengagement.